Tension Free mesh Hernioplasty; a Review of 96 cases. - Aurangzeb, Mehmud (Journal of Postgraduate Medical Institute, 2011)
To record the experience of a non hernia specialist general surgeon with the tension free mesh Hernioplasty. Of the total, 67(70%) ases were performed under local ansaesthesia; the remaining 29 (30%) had genral anaesthesia. This is a prospective study of 96 men that underwent the Lichtenstein tension free mesh hernioplasty, from February 1997 to February 2000, a total period of three years. The study was conducted at the surgical department of Khyber Teaching Hospital. the study confirms the safety and efficacy of the TFM Hernioplasty as a treatment modality for inguinal hernias. Furthermore the study also reveals the fact that similar results to those reported by the Lichtenstein Clinic can be reproduced in the hands of the real world of general surgeons.